The Riddle of Ball Lightning: A Review - José Donoso; José Luis Trueba; Antonio F. Rañada (The Scientific World Journal)
One of the most intriguing and enduring scientific challenges is to find an explanation for ball lightning, the shining fireballs that sometimes appear near lightning strokes. Although many theoretical ideas have been proposed and much experimental work has been performed, there is not yet an accepted explanation of their amazing properties. They are surprisingly stable, lasting up to 10 s, even minutes in some rare cases. By night, their appearance can be spectacular, but their brilliance is just similar to that of a home electric bulb. Most of the time, their motion is smooth and horizontal, but it can also be erratic and chaotic; they can penetrate indoors through window panes. We review here some of the most discussed approaches, including both theoretical models to find an explanation as well as experimental efforts to reproduce them in the laboratory. We distinguish between chemical and physical models, depending on whether their stability is mainly based on their chemical composition or on purely physical phenomena involving electromagnetic fields and plasmas.